2018
DOI: 10.1186/s12959-017-0157-x
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic assessment for patients with cancer and incidental pulmonary embolism

Abstract: BackgroundAn incidental/unsuspected diagnosis of pulmonary embolism (IPE) in cancer patients is a frequent occurrence. This single-institution analysis of uniformly managed patients investigates short and long-term outcomes and proposes a prognostic risk score, aiming to assist clinical decision-making.MethodsData from a prospectively recorded cohort of 234 consecutive cancer patients with IPE were analysed. Multivariate logistic regression and the Cox regression survival methods were used to identify factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…In the EPIPHANY study, the mortality rate was 14% in 30 days. However, the mortality risk increased in inpatient settings, symptomatic or suspicious PE, and abnormal vital signs [21,22]. In the current study, the enrolled patients had inpatient settings and suspicious PE.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In the EPIPHANY study, the mortality rate was 14% in 30 days. However, the mortality risk increased in inpatient settings, symptomatic or suspicious PE, and abnormal vital signs [21,22]. In the current study, the enrolled patients had inpatient settings and suspicious PE.…”
Section: Discussionmentioning
confidence: 72%
“…Nevertheless, high-risk PESI scores were significantly associated with three times higher mortality than in intermediate-risk PESI scores. In the previous studies, PESI tended to have a discriminatory power in cancer patients with PE [21]. However, the prognostic accuracy of PESI in patients with cancer diminished compared with its accuracy in the whole population [8].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Following the publication of this study [ 1 ] the authors identified the following errors inadvertently introduced during the production process: Within Table 1, under the sub-heading “Setting”, the numbers for the categories “Radical/adjuvant” and “Metastatic/incurable” were erroneously inversed. The correct numbers are: Radical/adjuvant: 20 (46) Metastatic/incurable: 80 (188) In Table 3, the values in the HR(95%CI) column were misaligned in the WCC rows; The value “1” should be aligned with the <11.3x10 9 row and the value 1.1 (.7, 1.8) should be aligned with the > 11.3x10 9 row.…”
Section: Correctionmentioning
confidence: 99%
“…[5][6][7][8][9] Recent retrospective research in cancer patients indicates that the embolic burden in IPE is similar to that in symptomatic PE. [10][11][12][13][14] Currently, all major guidelines recommend that the treatment of cancer patients with IPE should refer to the treatment of cancer patients with symptomatic PE. [15][16][17] Interestingly, the 2016 American College of Chest Physicians guideline suggests low-risk patients with isolated subsegmental PE (SSPE) receive no treatment in cases with normal bilateral ultrasonography of the legs (Grade 2C).…”
Section: Introductionmentioning
confidence: 99%